TECHNOLOGY, PHYSICO-CHEMICAL AND SENSORY CHARACTERISTICS OF INDIGENOUS GOAT CHEESE LIDER (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
The technology and quality of indigenous Lider goat cheese are examined in this research. It is a hard, full-fat cheese produced from pasteurized goat’s milk. Goat’s milk is obtained from goats that are raised in the mountainous area of Nikšić, Montenegro. The aim of the work is to present the Lider goat cheese technology as well as to examine the physico-chemical and sensory characteristics of this cheese. Cheese samples were tested after ripening for 21 days (three weeks). The average chemical composition of the cheese was (g/100 g): dry matter 61.85; fat 30.17; proteins 27.59; salt 3.96 and lactic acid 0.185. The average content of fat on dry basis (FDM), moisture on fat-free basis (MFFB) and salt in moisture (S/M) were 48.94%, 54.42% and 10.89%. Average pH was 5.25, water activity 0.895, while hardness and adhesiveness were 13.844N and -0.213N. The average rind thickness of 2.57 mm was established, while the average cross-sectional height and cross-sectional area of the cheese were 33.33 mm and 9.57 cm2/100g. The average density of the cheese was 1.338 g/ml. The total sensory evaluation averaged 17.34, which places this cheese in the high first class. One-way analysis of variance (p<0.05) revealed that there is a statistically significant influence of the production day on all physico-chemical and sensory parameters of the cheese, except for the external appearance and color.